Marketing strategy of the brand NIVEA aiming at consumers aged 20-40 on the Czech market - Kalmárová, Dominika (2025)
This thesis examines how Czech consumers aged 20 to 40 perceive the NIVEA brand and its marketing communication. The theoretical part includes trends in the cosmetics industry, consumer behaviour and a detailed look at the NIVEA brand, including its history, portfolio, sustainability efforts and marketing strategies. The practical part includes both quantitative and qualitative research focusing on consumer attitudes, purchasing behaviour and brand expectations. The thesis offers an insight into how the NIVEA brand is perceived on the Czech market and how its communication is in line with consumer preferences and current trends.